2021
DOI: 10.3389/fmicb.2021.571212
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus pumilus Group Comparative Genomics: Toward Pangenome Features, Diversity, and Marine Environmental Adaptation

Abstract: BackgroundMembers of the Bacillus pumilus group (abbreviated as the Bp group) are quite diverse and ubiquitous in marine environments, but little is known about correlation with their terrestrial counterparts. In this study, 16 marine strains that we had isolated before were sequenced and comparative genome analyses were performed with a total of 52 Bp group strains. The analyses included 20 marine isolates (which included the 16 new strains) and 32 terrestrial isolates, and their evolutionary relationships, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 117 publications
4
21
0
Order By: Relevance
“…2B). Due to the several taxonomic misclassifications of strains belonging to the Bacillus pumilus group (as reported here and by others (Espariz et al, 2016;X. Fu et al, 2021;Liu et al, 2013)), it is likely that strain C1 truly belongs to a B. safensis species; however, complete genome of C1 is not available to confirm this hypothesis.…”
Section: C-terminal Residues Differentiate Cynd From B Pumilus and B Safensismentioning
confidence: 57%
See 2 more Smart Citations
“…2B). Due to the several taxonomic misclassifications of strains belonging to the Bacillus pumilus group (as reported here and by others (Espariz et al, 2016;X. Fu et al, 2021;Liu et al, 2013)), it is likely that strain C1 truly belongs to a B. safensis species; however, complete genome of C1 is not available to confirm this hypothesis.…”
Section: C-terminal Residues Differentiate Cynd From B Pumilus and B Safensismentioning
confidence: 57%
“…1A, brown names) contains several strains already characterized as Bacillus altitudinis by different methods (for instance: BA06, ku-bf1, B-388 (X. Fu et al, 2021)) and also 4 strains (TUAT1, MTCB 6033, SH-B11 and C4) previously annotated as Bacillus pumilus. However, our analysis clearly demonstrates that they belong to Bacillus altitudinis and therefore require reclassification (Table S5) as previously suggested (Espariz et al, 2016;X.…”
Section: Bacillus Sp Per-urp-08 Is Classified As Bacillus Safensis Based On Core-genome Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four strains, namely, TUAT1, MTCC B6033, SH-B11, and C4, formed a separate cluster that had less than 95% homology with other strains of B. pumilus . In a previous study, it has been reported that three strains, namely TUAT1, MTCC B6033 and SH-B11 cluster with other B. altitudinis [ 41 ]. Our findings confirm this conclusion and place the C4 strain under B. altitudinis .…”
Section: Resultsmentioning
confidence: 99%
“…nov. Halomonas stenophila Tamlana crocina, sp. nov. 24,74,75 . In seeds of C. armena Novosphingobium was determined.…”
Section: Discussionmentioning
confidence: 99%